Students' Environmentally-Friendly Behavior: The Mediating Effect Investigation - Desnita, D.; Usmeldi, U.; Hidayat, H. (Jurnal Pendidikan IPA Indonesia, 2023)
The discovery of problems linked to environmentally-friendly behavior and several antecedent factors motivates this study. This study examines the effect of environmental physics understanding, scientific reasoning, and environmental behavior intentions on environmentally-friendly behavior and investigates the mediating role of scientific reasoning and environmental behavior intentions. This quantitative study used an associative approach. The research population was high schoolers in West Sumatra. The research sample was 407 high schoolers in West Sumatra, obtained through convenience sampling. Data were collected by applying a questionnaire. The research objectives were answered with a structural equation modeling approach. In this study, environmental physics understanding, scientific reasoning, and environmental behavior intentions are significant predictors of environmentally-friendly behavior. The results show that scientific reasoning had a mediating effect on the relationship between environmental physics understanding and environmentally-friendly behavior (β= 0.098, t = 1.794, p-value = 0.006). The environmental behavior intention has no mediating effect on the relationship between scientific reasoning on environmentally-friendly behavior (β= 0.045, t = 1.843, p-value = 0.066) and environmental physics understanding on environmentally-friendly behavior (β = 0.018, t = 1.467, p-value = 0.143). This study has limitations where data are only collected in high schools in West Sumatra, so generalizations are limited. Cross-sectional data add a further limitation to it. Conversely, this research augments the current literature on environmental physics understanding, scientific reasoning, and environmental behavior intentions by focusing on previously unstudied environmentally-friendly behavior. Furthermore, this study offers a novel theoretical explanation for the relationship between realizing the mediating role of scientific reasoning and environmental behavior intentions.